KETAHANAN PANGAN RUMAHTANGGA MISKIN PEDESAAN - Rita Hanafie (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2005)
Food diversification as effort to increase food security, one of which is conducted by promoting the society’s awareness in consuming varieties of food using a balance of nutrition principle. Though it has been implemented for nearly 40 years, food consumption diversification as the main component of food security, especially for the poor families at villages, has not run as it has been expected. This study reveals that the food consumption of the poor household has not fulfilled the criteria of four healthy the consumption of energy is 60,40% AKE and the protein is 34,31% AKP, had not reflected the food security condition. The food consumption dversification quality score is only 23,69%. Only one fod group, namely beans was consumed with the proportion nearly PPH norm, two fod grops, namely tubers and fruits.oliy seed were consumed beynd the normative proportion and the five groups of food, namely rice, animal food, fat oil, sugar and vegetables and fruit were consumed under the normative proportion.